Transcriptome Analyses Reveal Candidate Pod Shattering-Associated Genes Involved in the Pod Ventral Sutures of Common Vetch (Vicia sativa L.) - Dong, Rui; Dong, Deke; Luo, Dong; Zhou, Qiang; Chai, Xutian; Zhang, Jiyu; Xie, Wengang; Liu, Wenxian; Dong, Yang; Wang, Yanrong; Liu, Zhipeng (Frontiers in Plant Science, 2017)
The seed dispersion caused by pod shattering is a form of propagation used by many wild species. Loss of seeds from pod shattering is frequent in the common vetch (Vicia sativa L.), an important self-pollinating annual forage legume. However, pod shattering is one of the most important defects that limits the reproduction of the vetch in the field and the usage as a leguminous forage crop. To better understand the vetch pod shattering mechanism, we used high-throughput RNA sequencing to assess the global changes in the transcriptomes of the pod ventral sutures of shattering-susceptible and shattering-resistant vetch accessions screened from 541 vetch germplasms. A total of 1,285 significantly differentially expressed unigenes (DEGs) were detected, including 575 up-regulated unigenes and 710 down-regulated unigenes. Analyses of Gene Ontology and KEGG metabolic enrichment pathways of 1,285 DEGs indicated that 22 DEGs encoding cell wall modifications and hydrolases associated with pod shattering were highly expressed in shattering-susceptible accessions. These genes were mainly enriched in “hydrolase activity,” “cytoplasm,” and “carbohydrate metabolic process” systems. These cell wall modifications and hydrolases genes included β-glucosidase and endo-polygalacturonase, which work together to break down the glycosidic bonds of pectin and cellulose, and to promote the dissolution and disappearance of the cell wall in the ventral suture of the pod and make the pod more susceptible to shattering. We demonstrated the differences in gene transcription levels between the shattering-susceptible and shattering-resistant vetch accessions for the first time and our results provided valuable information for the identifying and characterizing of pod shattering regulation networks in vetch. This information may facilitate the future identification of pod shattering-related genes and their underlying molecular mechanisms in the common vetch.